Phantom k-essence cosmologies - Aguirregabiria, Juan M. (2004)
We devise a method to obtain a phantom version of FRW k-essence cosmologies with homogeneous k fields by applying form-invariance transformations. It can be seen that the transformation performs the maps [Formula Presented] and [Formula Presented] which in turn give [Formula Presented] and [Formula Presented] The discussion is presented in a general setup, valid for FRW k-essence cosmologies, and then we discuss power-law solutions for illustration purposes. First, we deal with models such that the gradient of the k field is not constant, and they include standard and generalized tachyon cosmologies. We concentrate on the usual tachyon and show that the phantom symmetry involves a change in the potential: and that it generates an extended superaccelerated tachyon field. Then, we turn our attention to models for which the time derivative of the k field is not constant, and we show the transformation can be implemented without changing the potential at all. © 2004 The American Physical Society.